Risk Factors of Hypersensitivity to Carboplatin in Patients with Gynecologic Malignancies - Tai, Yu-Hsiao; Tai, Yi-Jou; Hsu, Heng-Cheng; Lee, Shu-Ping; Chen, Yun-Yuan; Chiang, Ying-Cheng; Chen, Yu-Li; Chen, Chi-An; Cheng, Wen-Fang (Frontiers in Pharmacology, 2017)
We evaluated the prevalence of and risk factors for hypersensitivity reactions related to carboplatin, which is commonly used to treat gynecological malignancies. All women with pathologically documented ovarian, fallopian tube, or primary peritoneal cancer treated with carboplatin alone or a carboplatin-based combination chemotherapy regimen at a single hospital between January 2006 and December 2013 were retrospectively recruited. We analyzed the incidence, characteristics, risk factors, management, and outcomes of carboplatin-related hypersensitivity reactions among these patients. Among 735 eligible women, 75 (10.2%) experienced a total of 215 carboplatin-related hypersensitivity reaction events. The annual incidence of carboplatin-related hypersensitivity reactions gradually increased from 0.88% in 2006 to 5.42% in 2013. The incidence of carboplatin-related hypersensitivity was higher in patients with advanced stage disease (P<.001, Kruskal-Wallis test), serous and mixed histological types (P=.003, Kruskal-Wallis test), malignant ascites (P=.009, chi-square test), and history of other drug allergy (P<.001, chi-square test). Compared to women without hypersensitivity reactions, women who experienced hypersensitivity reactions had a significantly greater median cycle number (12 vs. 6, P<.001, independent sample t-test) and dose (6,816 vs. 3,844 mg, P<.001, independent sample t-test). The cumulative incidence of carboplatin-related hypersensitivity reactions dramatically increased with >8 cycles or dose >3,500 mg. Therefore, disease severity, histological type, malignant ascites, past drug allergies, and cumulative carboplatin dose are risk factors for carboplatin-related hypersensitivity reactions. Such reactions could potentially be reduced or prevented by slowing the infusion rate and using a desensitization protocol involving anti-allergy medications.